2013
DOI: 10.1097/jcp.0b013e31828b50a7
|View full text |Cite
|
Sign up to set email alerts
|

Memantine Add-On to Risperidone for Treatment of Negative Symptoms in Patients With Stable Schizophrenia

Abstract: We aimed to evaluate the efficacy of memantine add-on in the treatment of primary negative symptoms of patients with stable schizophrenia. In a double-blind placebo-controlled clinical trial, 40 patients with schizophrenia (Diagnostic and Statistical Manual of Mental Disorders, Fourth Edition) who were stabilized on risperidone for a minimum of 8 weeks were randomized to either memantine (20 mg) or placebo in addition to risperidone, 6 mg/d, for eight weeks. Assessment was done using the Positive and Negative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(36 citation statements)
references
References 49 publications
0
36
0
Order By: Relevance
“…A meta‐analysis of NMDAR agonists as adjunctive therapies for schizophrenia accordingly showed that NMDAR agonists are superior to placebo in terms of overall and negative symptoms . In contrast with NMDAR agonists, the NMDAR antagonists amantadine and memantine (MEM) improved cognitive impairments of schizophrenia according to another meta‐analysis, and adjuvant medication with MEM and antipsychotics was effective on positive, negative, and cognitive symptoms in schizophrenia . Other clinical studies demonstrate clinical benefits of MEM against several psychiatric disorders, including mood and anxiety disorders and schizophrenia …”
Section: Introductionmentioning
confidence: 99%
“…A meta‐analysis of NMDAR agonists as adjunctive therapies for schizophrenia accordingly showed that NMDAR agonists are superior to placebo in terms of overall and negative symptoms . In contrast with NMDAR agonists, the NMDAR antagonists amantadine and memantine (MEM) improved cognitive impairments of schizophrenia according to another meta‐analysis, and adjuvant medication with MEM and antipsychotics was effective on positive, negative, and cognitive symptoms in schizophrenia . Other clinical studies demonstrate clinical benefits of MEM against several psychiatric disorders, including mood and anxiety disorders and schizophrenia …”
Section: Introductionmentioning
confidence: 99%
“…Rezaei et al [16] in their study used the same combination of medications as we did—risperidone + memantine—for tackling the negative symptoms in their sample. The authors suggested that, in order to evaluate improvement in primary negative symptoms, it is essential that the patient should be depression-free and without positive or extrapyramidal symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…However, the few randomized double-blind placebo controlled studies that have evaluated the effi cacy of add-on memantine have shown mixed results. Memantine, when used as add-on therapy to on-going treatment with atypical antipsychotics in patients with schizophrenia having residual symptoms showed signifi cant benefi t in improving residual symptoms when assessed at 8 weeks posttreatment in one study [ 18 ] while another study reported negative fi ndings [ 19 ] . In another double-blind placebo-controlled trial in patients with chronic schizophrenia, 12 weeks of adjunctive therapy with memantine did not improve psychopathology or cognitive functioning; however, memantine was tolerated well and did not exacerbate positive symptoms [ 20 ] .…”
Section: Off -Label Use Of Memantine As Adjunctive Treatment In Schizmentioning
confidence: 99%